"Typographicum robur fractum" - Desmet, Marc (De musica disserenda, 2007)
This article develops a new hypothesis concerning the link between the composer Jacob Handl and the sphere of typography, notably through the influence and activity as a printer of Georg Handl, Jacob's brother. The production of Georg Handl the printer is examined; this can shed light on the reputation and make-up of Jacob's own printed output.
Keywords: Gallus, Jacobus, 1550-1591; Handl, Georg; Olomouc; glasbena tipografija